2014
DOI: 10.2514/1.c032189
|View full text |Cite
|
Sign up to set email alerts
|

Sonic-Boom Mitigation Through Aircraft Design and Adjoint Methodology

Abstract: This paper presents a novel approach to design of the supersonic aircraft outer mold line (OML) by optimizing the A-weighted loudness of sonic boom signature predicted on the ground. The optimization process uses the sensitivity information obtained by coupling the discrete adjoint formulations for the augmented Burgers Equation and Computational Fluid Dynamics (CFD) equations. This coupled formulation links the loudness of the ground boom signature to the aircraft geometry thus allowing efficient shape optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…6,11 Here, we illustrate that our new approach can handle the problem well. Figure 4 shows the calculated results obtained by using Burgers-Relax, in which the internal variable is included through Eq.…”
Section: A Improved Stability By Using the Present Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…6,11 Here, we illustrate that our new approach can handle the problem well. Figure 4 shows the calculated results obtained by using Burgers-Relax, in which the internal variable is included through Eq.…”
Section: A Improved Stability By Using the Present Methodsmentioning
confidence: 94%
“…Extensive efforts have focused on the fundamental design of the supersonic aircraft shape, which produces a lower level of the near-field pressure disturbance below the supersonic aircraft at a high altitude. [1][2][3][4][5][6] Evaluation methods of the sonic boom on the ground from the near-field one are required to confirm the validity of the shape so designed. Therefore, it is desirable to calculate the modification of the pressure disturbance generated by the aircraft during the propagation in an atmospheric air to the ground theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…99 These include the exploration of synergies between continued development of boundary layer modeling methods (e.g., wall functions, cut cells, immersed boundary, or integral boundary) with error estimates. The uncertainty quantification issues raised by Barth 100 will be addressed and unstructured grid adaptation will be extended to include the control of modeling errors.…”
Section: Iiib Ten Years: 2025mentioning
confidence: 99%
“…CFD-based shape optimization has been a key ingredient in meeting both the sonic-boom and aerodynamic performance goals. Some of the leading CFD-based sonic-boom shape optimization tools include the Cart3D adjoint code by Aftosmis [6] and the FUN3D adjoint/sBOOM tool by Park/Rallabhandi [7,8]. These tools couple parametric geometry, CFD near-field flow solutions, wave propagation, and ground-level sound metric computation into a single design tool with sonic-boom and performance as the objective function.…”
Section: Introductionmentioning
confidence: 99%
“…Ground and flight test validation is required to answer these questions. In 2003, the DARPA Quiet Supersonic Platform (QSP) Shaped Sonic Boom Demonstrator (SSBD) program [8] showed that a shaped near-field signature does persist to the ground. In this flight experiment the front portion of an F-5E fuselage was modified to produce a shaped front-side ground signature.…”
Section: Introductionmentioning
confidence: 99%